IMPLEMENTATION OF LOCAL WISDOM IN LEARNING IN SCHOOLS AROUND RURAL AREAS - Melyana R Pugu; Noneng Nurhayani; Farida Asy'ari (CV. ADIBA ASIHA AMIRA, 2024)
The study aims to explore the implementation of local wisdom in learning in schools in rural areas, focusing on how local Wisdom can be integrated into the learning process to improve the relevance and effectiveness of education. The study reveals the contribution of local wisdom in educating students about identities and traditions of communities, as well as its role in strengthening character education and preserving cultural values in the face of global influence and modern technology. This research is carried out through a literature review, which involves the collection and analysis of secondary data from relevant sources, including scientific journals, articles, research reports, and online sources. Through this method, research identifies, analyzes, and synthesizes findings from previous research related to the implementation of local wisdom in education, especially in rural areas. Research results show that the implementation of local wisdom in learning in rural schools has significant potential in enriching student curricula and learning experiences. Local wisdom, when integrated into learning, can enhance students' understanding of their socio-cultural environment and local history, while facilitating the building of identity and appreciation of cultural heritage. In addition, learning strategies that leverage local wisdom have proven effective in developing students' critical skills, problem-solving skills, and project-based learning relevant to their local context. Obstacles identified include resource shortages, the need for teacher training for innovative learning strategies, and the challenge of integrating local content with national educational standards. The research reaffirms the importance of collaboration between schools, communities, and stakeholders in encouraging and nurturing the implementation of local wisdom in education.